Design of an efficient coherent multi-site single-molecule rectifier. Issue 43 (25th October 2017) - Perrin, Mickael L.; Doelman, Matthijs; Eelkema, Rienk; van der Zant, Herre S. J.
Abstract : We propose the design of a multi-site single-molecule diode with a rectification ratio exceeding a million. Abstract : We propose the design of a single-molecule diode with a rectification ratio exceeding a million. The employed mechanism is based on coherent resonant charge transport across a molecule that consists of four conjugated sites coupled by non-conjugated bridges. Using density functional theory calculations, we rationalize the design of the molecule and demonstrate the crucial role of aligning the sites at a specific voltage. Rectification ratios are calculated for a series of chemical substituents and demonstrate that with careful molecular design, high rectification ratios can be achieved. Finally, we comment on the shortcomings of our approach, how further improvements can be obtained and discuss some of the experimental challenges.